Diagnostic concordance of ultrasound and histopathology in pediatric neck masses - Monowara, Mahmuda; Parvez, Mashud; Jannat, Shakila (International Journal of Research in Medical Sciences, 2025)
Background: Ultrasonography has become the most accessible, safe, and cost-effective imaging modality for evaluating pediatric neck masses, especially in resource-limited settings. The purpose of the study was to assess the diagnostic concordance between ultrasound findings and histopathological results in pediatric neck masses. The aim of the study was to evaluate the diagnostic concordance between ultrasound findings and histopathological results in pediatric neck masses. Methods: This observational diagnostic study was conducted at Bangladesh Shishu hospital and institute from October 2023 to March 2025, involving 550 children (0-12 years) with palpable neck masses. All cases underwent ultrasound and confirmatory histopathological examination. Diagnoses were made independently by radiologists and blinded pathologists. Concordance was defined as an exact diagnostic match. Data were analyzed using SPSS v28 with descriptive statistics. Results: Among 550 pediatric patients with neck masses, most were aged >2-5 years (50.9%) with a balanced gender distribution. Lymphadenitis was the most common ultrasound (40.6%) and histopathological (34.2%) finding. Congenital lesions like cystic hygromas, thyroglossal duct cysts, and haemangiomas were also frequent. Ultrasound showed high diagnostic concordance, particularly for cystic hygromas (98.0%), thyroglossal duct cysts (97.7%), and branchial cleft cysts (96.2%), with an overall concordance rate of 90.0%. Conclusions: Ultrasound demonstrates high concordance with histopathology, reinforcing its value as a reliable, non-invasive first-line diagnostic tool for pediatric neck masses.